'Menjadi Jawa': Naskah Cina-Jawa - Dwi Woro Retno Mastuti (Masyarakat Pernaskahan Nusantara, 2011)
Chinese-Javanese manuscripts, written in the Javanese language and script, are part of the treasury of Javanese manuscripts that have existed since the early 19th century. The content of these manuscripts narrates Chinese myths and legends, such as Sam Kok and Sik Jin Kwi. There are 118 Chinese-Javanese manuscripts scattered across various libraries on the island of Java and abroad. These manuscripts serve as evidence of the writing activities of the Chinese Peranakan community in Java. Furthermore, they evidence the efforts of ethnic Chinese residing in Java during that period to 'become Javanese'. The aksara swara (vowel characters) and aksara rekan (foreign sound characters) appearing in Chinese-Javanese manuscripts are also 'new formations' created to maintain Chinese identity. These scripts were used to spell the names of characters within the story texts. === Naskah-naskah Cina-Jawa, yang ditulis dalam bahasa/aksara Jawa merupakan bagian dari khasanah naskah Jawa yang telah hadir sejak awal abad ke-19. Isi naskah tersebut mengisahkan mitos/legenda Tiongkok, seperti Sam Kok dan Sik Jin Kwi. Jumlah naskah-naskah Cina-Jawa adalah 118 tersebar di berbagai perpustakaan di pulau Jawa dan mancanegara. Naskah ini merupakan bukti aktifitas masyarakat Cina Peranakan Jawa di bidang tradisi tulis. Selain itu juga bukti upaya 'menjadi Jawa' etnis Cina yang pada masa itu tinggal di Pulau Jawa. Aksara swara dan aksara rekan yang muncul dalam naskah Cina-Jawa juga merupakan 'bentukan baru' yang diciptakan untuk tetap memunculkan identitas kecinaan. Aksara tersebut digunakan untuk menulis nama-nama tokoh dalam teks cerita.